PENGARUH PENGGUNAAN TEPUNG AMPAS KECAP DALAM PAKAN AYAM PETELUR FASE MENJELANG AFKIR TERHADAP KADAR PROTEIN DAN VITAMIN A, SERTA MASSA PROTEIN TELUR (The Usage Effect of Soy Sauce Waste Product in Feed of Laying Hens on Protein and Vitamin A Percentage, and Protein Mass of Egg) - D. Pilsari; L. D. Mahfudz; U. Atmomarsono (Jurnal Ilmu dan Teknologi Peternakan, 2017)
The study was aimed to examine the effect of soy sauce waste product in in the diet of laying hens on protein percentage, protein mass and vitamin A percentage of whole eggs also income over feed cost (IOFC). The material used were 200 birds of Lohman Brown at 80 weeks old, with average body weight 1.932,75±189,50 g. Feed ingridient were yellow corn, rice bran, soybean meal, fsh meal, meat bone meal, poultry meat meal,  lysine, methionine,  limestone powder, premix and soy sauce waste product. The  experimental design used was  completely  randomized design  (CRD) with  4 treatments and 5 replications, total 20 unit experiments and each unit contains 10 laying hens. The observed variables were protein percentage, protein mass and vitamin A percentage of whole eggs. The data was analyzed using analysis of variance (ANOVA) with F test, if there are signifcant effect of treatment continued to Duncant test. The result showed that the usage of soy sauce waste product in diet of laying hens were signifcantly (p<0,05) decrease protein percentage and protein mass of whole egg, but did not effected on whole egg vitamin A. Soy sauce waste product can be used as laying hans feed until 15% with the higher IOFC.